2014
DOI: 10.1074/jbc.m113.535955
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage to a Single Chromosome End Delays Anaphase Onset

Abstract: Background: DNA repair on mitotic chromosomes is attenuated. However, the response of specific chromosomal domains has not been studied. Results: Damage to a single chromosome tip, but not arms, during mitosis results in a localized DNA damage response and anaphase onset delay. Conclusion: DNA damage induced at chromosome tips and arms in mitosis has different consequences. Significance: These findings provide the first evidence of a chromosome locus-specific DNA damage response in mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 74 publications
(68 reference statements)
0
25
0
Order By: Relevance
“…After phosphorylation and activation by Chk2, p53 induces the expression of p21, a well-known cyclin dependent kinase inhibitors (CDKI) that inactivates cyclin dependent kinase 2 (CDK2) to prevent G1/S phase progression (Jiang and Dong 2008; Miller et al 2010; Oh et al 2014; Pabla and Dong 2008; Price et al 2004a; Price et al 2009; Zannini et al 2014). Alternatively, Chk2 induces cell division cycle 25 homolog C (cdc25C) phosphorylation and translocation from nuclei to cytosol and, as a result, cdc25C can no longer activate CDK1 for G2/M phase progression and result in cell cycle arrest at G2/M (Silva et al 2014; Thomasova and Anders 2014; Zannini et al 2014). …”
Section: Dna Damage Responsementioning
confidence: 99%
“…After phosphorylation and activation by Chk2, p53 induces the expression of p21, a well-known cyclin dependent kinase inhibitors (CDKI) that inactivates cyclin dependent kinase 2 (CDK2) to prevent G1/S phase progression (Jiang and Dong 2008; Miller et al 2010; Oh et al 2014; Pabla and Dong 2008; Price et al 2004a; Price et al 2009; Zannini et al 2014). Alternatively, Chk2 induces cell division cycle 25 homolog C (cdc25C) phosphorylation and translocation from nuclei to cytosol and, as a result, cdc25C can no longer activate CDK1 for G2/M phase progression and result in cell cycle arrest at G2/M (Silva et al 2014; Thomasova and Anders 2014; Zannini et al 2014). …”
Section: Dna Damage Responsementioning
confidence: 99%
“…Studies by our lab and others have shown the ability of a diffraction-limited focused near-infrared (NIR) 780nm laser micro-beam to induce DSBs marked by γH2AX, phosphorylated Histone H2AX on Ser 139, and KU in both interphase and mitosis [29, 3137]. In addition to γH2AX and KU at laser-damaged sites, we have demonstrated that ubiquitylation was also occurring at damage sites in mitosis [28, 29].…”
Section: Introductionmentioning
confidence: 84%
“…These methods of DNA damage induction result in genome-wide alterations that may lead to different DDRs. However, the laser has demonstrated to be very useful for DNA damage response studies because of its ability to target a submicron region within a specified chromosome region [2329]. Interestingly, a laser micro-irradiation study conducted over forty years ago, showed that when the nucleolar organizer was specifically damaged in mitotic cells, a few of the irradiated cells were able to undergo a subsequent mitosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using laser microirradiation, DNA damage-induced changes of the free and bound fractions of NADH were measured by FLIM in the cytoplasm and nucleus in HeLa cells. Laser microirradiation can be used to induce DNA damage in a highly controlled fashion (16,(37)(38)(39)(40).…”
Section: Phasor-approach To Flim Reveals Ratiometric Increase Of Protmentioning
confidence: 99%